Ekstrak Etanol Ubi Jalar Ungu untuk Mencegah Peningkatan pH Vagina setelah Ovariektomi Bilateral pada Tikus Wistar - Sugiritama, I Wayan; Sri Wiryawan, I Gusti Nyoman; Linawati, Ni Made; Wahyuniari, Ida Ayu Ika; Ratnayanthi, I Gusti Ayu Dewi; Arijana, I Gusti Nyoman Kamasan (Jurnal Kefarmasian Indonesia, 2022)
AVaginal atrophy is one of the most common health problems in postmenopausal women. The disease is characterized by decreasing layers and maturation index of the vaginal epithelium and an increase in vaginal pH. A decrease in vaginal acidity will increase the susceptibility to infections since acidic pH protects the vagina from pathogens infection. The previous study has proven that phytoestrogens were effective to improve the microstructures of the vaginal, reduce urogenital complaints, and improve vaginal pH. The purple sweet potato (Ipomea batatas L.) which is cultivated in Bali was recognized for its high anthocyanin content and was reported to have phytoestrogen activity. The aim of the present study is to evaluate the effect of purple sweet potato on vaginal pH in an animal model of menopause. The randomized pre-test post-test control group design study was conducted using 36 bilateral ovariectomized female Wistar rats as an animal model of menopause. The animals were divided randomly into a control group (T0) which was given saline and a treatment group (T1) given an ethanolic extract of purple sweet potato 400 mg/day for 30 days. Vaginal pH was measured before treatment, every week during treatment, and after treatment. The result of the study showed that there was an increase in vaginal pH of the T0 on the 2nd and 3rd week, and after treatment (P